Effects of Spiritual Guided Imagery and Music on Hemodynamic Status of Cancer Patients Undergoing Chemotherapy - Jonas Edrian Sumampouw; Yourisna Pasambo; Muh. Ali Makaminan (Universitas Aisyah Pringsewu, 2021)
Spiritual Guided Imagery and Music (SGIM) is a Mind, Body, and Spirit therapy that has been used for several years in nursing for the management of anxiety of patients with cancer. This study aimed to investigate the effects of SGIM on the hemodynamic status of cancer patients undergoing chemotherapy. The study was a quasi-experimental study, with 30 patients who received SGIM therapy and 30 as a control group. The hemodynamic status measured in this study consisted of Blood Pressure (BP), heart rate, respiratory rate, and oxygen saturation. Hemodynamic status was measured 3 times: 1 day and 30 minutes before chemotherapy and 1 day after chemotherapy. Data were analyzed by GLM repeated-measures test with SPSS 21. The analysis of the GLM repeated measure test has a known p-value less than 0.05 for systolic and diastolic BP, Mean Arterial Pressure, and heart rate, whilst the effects of SGIM on respiratory rate and oxygen saturation there was no significant difference between the two groups but still in the normal range. SGIM Therapy can improve the hemodynamic status of cancer patients undergoing chemotherapy. this therapy can be applied as one of the complementary therapies for cancer patients undergoing chemotherapy. Spiritual Guided Imagery and Music (SGIM) adalah mind, body dan spirit terapi yang telah digunakan selama beberapa tahun dalam keperawata, untuk mengatasi kecemasan pasien kanker. Penelitian ini bertujuan untuk mengetahui pengaruh SGIM terhadap status hemodinamik pasien kanker selama menjalani kemoterapi. Penelitian ini merupakan penelitian eksperimen semu, dengan 30 pasien yang mendapat terapi SGIM dan 30 sebagai kelompok kontrol. Status hemodinamik yang diukur dalam penelitian ini terdiri dari Tekanan Darah (BP), denyut jantung, laju pernapasan, dan saturasi oksigen. Status hemodinamik diukur 3 kali: 1 hari dan 30 menit sebelum kemoterapi dan 1 hari setelah kemoterapi. Data dianalisis dengan menggunakan uji GLM repeated measure dengan bantuan SPSS 21. Analisis uji GLM repeated measure diketahui p-value kurang dari 0,05 untuk TD sistolik dan diastolik, Mean Arterial Pressure, dan denyut jantung, sedangkan efek SGIM pada laju pernapasan dan saturasi oksigen tidak ada perbedaan yang signifikan antara kedua kelompok, tetapi masih dalam kisaran normal. Terapi SGIM dapat memperbaiki status hemodinamik pasien kanker yang menjalani kemoterapi. Terapi ini dapat diterapkan sebagai salah satu terapi komplementer bagi pasien kanker yang menjalani kemoterapi.